Cytotoxicity and inflammatory response of different types of provisional restorative materials - Campaner, Marcio [UNESP]; Takamiya, Aline Satie [UNESP]; Bitencourt, Sandro Basso [UNESP]; Mazza, Leticia Cerri [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; Shibayama, Ricardo; Barão, Valentim Adelino Ricardo; Sukotjo, Cortino; Pesqueira, Aldiéris Alves [UNESP] (Elsevier, 2020)
Aim: To evaluate the cytotoxicity and inflammatory response of different types of provisional restorative materials to mice gingival fibroblasts. Methods: Cytotoxicity of provisional material discs (thermal-polymerized acrylic resin; auto-polymerized acrylic resin; bisacrylic resin; nano-ceramic resin for CAD/CAM and prefabricated polymer block for CAD/CAM) to Mice (Balb/c) gingival cell were investigated under direct and indirect contact (extracts) at 24, 48 and 72 h, using the MTT and Alamar blue assays. Materials extracts (24 h) were applied to the cell culture (indirect contact) or cells were seeded on discs of provisional materials, and the cytotoxicity and production of IL-6, IL-1β and TNF-α after 24, 48 and 72 h were analyzed through MTT, Alamar Blue® and ELISA. Culture medium was used as control for indirect contact assay (extract) and the surfaces of the wells without discs of provisional materials were used as control for direct contact assay. Results were analysed statistically by ANOVA followed by the Bonferroni-Test correction. Statistically significant differences were considered if P was < .05. Results: Auto-polymerized and bisacrylic resins (direct contact) reduced cell viability after 24, 48 and 72 h compared to control (P < .05). Indirect contact (extract) was not cytotoxic to cells at all periods compared to control (P > .05). Auto-polymerized and bisacrylic resins increased IL-6, IL-1β and TNF-α levels mainly at 24 h when compared to the other materials (P < .001). Conclusion: Auto-polymerized and bisacrylic were more cytotoxic to mice gingival fibroblasts. CAD/CAM nano ceramic resin and prefabricated polymer blocks are more predictable materials to preserve the periodontal soft tissues.
Keywords: Acrylic resins; Computer-aided design; Fixed partial denture; Materials testing